DESIGNING QURANIC APPLICATIONS AND PRAYER SCHEDULES WITH ALGORITHM METHOD KNUTH MORRIS PRATT ANDROID-BASED - Widya, Helma; Alam, Hermansyah; Harahap, Partaonan (RELE (Rekayasa Elektrikal dan Energi) : Jurnal Teknik Elektro, 2023)
Reading the Qur'an is one of the obligations of a Muslim, because in the Qur'an there are guidelines for every human being to always walk on the path that Allah Almighty permits. Allah Almighty has promised in the Qur'an that anyone who reads the Qur'an will never get a loss but on the contrary, they will get double reward. The purpose of this research is to design the Qur'an Application through a communication tool called a smartphone. The result of this design to see the prayer schedule which consists of several menus and make it easier for the user of smartphobe to read the Qur'an and also to see the prayer schedule gradually.